Sistem Informasi Distribusi LPG 3 Kg Pada PT Explorindo Solusi Gasindo Kudus Berbasis Website - Kusdariyanto, Sofiyan (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2025)
The 3 kg LPG distribution system plays an important role in ensuring the fuel supply is well-targeted. 3 kg Liquefied Petroleum Gas (LPG) is an important subsidized fuel for households and small businesses in Indonesia. PT Explorindo Solusi Gasindo Kudus faces obstacles in the distribution and management of new base registration manually, such as long lines, data errors, and payment complexity. This research develops a web-based information system to improve administrative efficiency, simplify registration, and increase service transparency. This research aims to develop a web-based LPG 3 KG Distribution Information System for PT Explorindo Solusi Gasindo Kudus. This system is designed to facilitate distribution data management, including base registration, cross-check for base acceptance, and real-time base data reporting. This system is expected to support modern and effective management of LPG distribution. The implementation results show an increase in operational efficiency, data transparency, and ease of access for related parties, supporting the optimization of LPG distribution in the Kudus area.